2014
DOI: 10.3892/ol.2014.1864
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant expression of redox protein Ape1 in colon cancer stem cells

Abstract: Ape1 is an important redox protein, essential for specific cytokine-induced signal transduction. Ape1 signaling is also important in regulating the growth of cancer cells, including colon cancer cells. The present study investigated whether Ape1 signaling plays a role in the regulation of colon cancer stem cell (CCSC) growth. The results showed that Ape1 was aberrantly expressed in CCSCs, as determined by quantitative (q)PCR assay. A laser confocal microscopy assay demonstrated that the Ape1 protein was mainly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 19 publications
0
47
0
Order By: Relevance
“…Combining APE1‐targeted agents with 5‐FU in tumors genetically similar to Pa02C should respond favorably to this combination due to reduced BCRP expression. A study in colon cancer stem cells indeed demonstrated dramatically increased cell killing when 5‐FU and an inhibitor of APE1, APX3330, were used in vivo (Lou et al ., 2014). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Combining APE1‐targeted agents with 5‐FU in tumors genetically similar to Pa02C should respond favorably to this combination due to reduced BCRP expression. A study in colon cancer stem cells indeed demonstrated dramatically increased cell killing when 5‐FU and an inhibitor of APE1, APX3330, were used in vivo (Lou et al ., 2014). …”
Section: Discussionmentioning
confidence: 99%
“…APE1 expression is increased in several cancers such as pancreatic (Jiang et al ., 2010), prostate (Kelley et al ., 2001), cervical (Xu et al ., 1997), gliomas (Bobola et al ., 2004), lung (Yoo et al ., 2008), bladder (Shin et al ., 2015), colon (Lou et al ., 2014), and ovarian cancers (Al‐Attar et al ., 2010; Zhang et al ., 2009), and this increase is associated with resistance to radiation and chemotherapy, leading to poorer patient prognosis (Sharbeen et al ., 2015). Based on its involvement in cancer, and its regulation of several transcription factors associated with cancer‐related pathways, APE1 has become a prime target for anticancer therapies (Fishel and Kelley, 2007; Kelley et al ., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…APE-1 has been linked to resistance to alkylating agents, such as temozolomide, in glioblastoma cells [Silber et al, 2002]. In addition, E3330 treatment has been found to sensitize colon cancer stem cells to 5-fluoruracil therapy, indicating that this inhibitor may play an important role in reducing chemoresistance [Lou et al, 2014]. In this study, cells treated with doxorubicin þ Co exhibited diminished HIF-1a activity following E3330 administration.…”
Section: Discussionmentioning
confidence: 62%
“…To assess the antiangiogenic activity of APX3330, the mice were i.p. injected with compound (50 mg/kg body weight), twice daily, five days on/two days off, as used previously in vivo (Fishel et al, 2011;Lou et al, 2014;Biswas et al, 2015). Vehicle was 4% Cremophor:ethanol (1:1) in PBS.…”
Section: Animalsmentioning
confidence: 99%